2015
DOI: 10.3727/096368913x674675
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Dental Pulp Stem Cells Support Human Umbilical Cord Blood-Derived Hematopoietic Stem/Progenitor Cells in Vitro

Abstract: It is well documented that specialized mesenchymal stem/stromal cells (MSCs) constitute the hematopoietic stem cell (HSC) niche in the bone marrow (BM), and these MSCs support/maintain the HSCs in an undifferentiated state. A number of studies have demonstrated that BM-derived MSCs (BM-MSCs) can support HSCs in vitro. However, it remains unclear whether nonhematopoietic tissue-derived MSC-like cells, such as dental pulp stem cells (DPSCs), have the ability to support HSCs. In this study, we prospectively isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(73 reference statements)
1
2
0
Order By: Relevance
“…We investigated the hematopoiesis-supporting properties of BM-derived MSCs obtained from different species. We found that mMSCs support the proliferation and migration of CD34 + hHSPCs in agreement with recent reports demonstrating the expansion of CD34 + hematopoietic cells in the presence of either murine stromal cell lines or mMSC-like cells derived from dental pulps 31 32 . Nonetheless, we observed subtle differences in their capacity to support certain hHSPC subpopulations and to maintain the HSPC polarization by comparing them to those derived from human tissues.…”
Section: Discussionsupporting
confidence: 92%
“…We investigated the hematopoiesis-supporting properties of BM-derived MSCs obtained from different species. We found that mMSCs support the proliferation and migration of CD34 + hHSPCs in agreement with recent reports demonstrating the expansion of CD34 + hematopoietic cells in the presence of either murine stromal cell lines or mMSC-like cells derived from dental pulps 31 32 . Nonetheless, we observed subtle differences in their capacity to support certain hHSPC subpopulations and to maintain the HSPC polarization by comparing them to those derived from human tissues.…”
Section: Discussionsupporting
confidence: 92%
“…DPSCs have been reported to possess many in vitro characteristics of mesenchymal stem cells (MSCs) with high clonogenicity and MSC marker expression [34][35][36][37][38][39][40] . However, the in vivo stem cell properties and physiological function of DPSCs in adult teeth remain elusive.…”
Section: Mx1 + Ocnpulp Cells Show High Expression Of Dental Pulp Stem...mentioning
confidence: 99%
“…MSCs derived from dental pulp tissue (DP-MSC) differ from the other MSCs because their embryonic origin is the neural crest [ 16 ]. Mouse DP-MSCs have been reported to support in vitro growth of human UCB-HSPCs [ 17 ]. The successful differentiation of MSCs from human iPSCs via a neural crest cell lineage by traditional monolayer cultures has been reported [ 13 ].…”
Section: Introductionmentioning
confidence: 99%